Kedudukan Legal Opinion sebagai Sumber Hukum - Ery Agus Priyono; Kornelius Benuf (Universitas Negeri Surabaya, 2020)
Law is a means to achieve the order and welfare of the community. One of the sources of law is doctrine. The doctrine is essentially the opinion of a legal expert on a real legal issue. When discussing legal opinions, the term legal opinion is also known. Doctrine and Legal Opinion are mostly the same, namely the legal opinion of a legal expert on a real legal problem. If we agree that Doctrine and Legal Opinion are the same way in much of the literature that is mentioned as a source of law is the only doctrine, whereas where is legal opinion placed in the formation of a law? This paper will explain the position of Legal opinion as a source of law.